2016
DOI: 10.1061/(asce)cp.1943-5487.0000524
|View full text |Cite
|
Sign up to set email alerts
|

Big-Data Approach for Three-Dimensional Building Extraction from Aerial Laser Scanning

Abstract: This paper proposes a Big Data approach to automatically identify and extract buildings from a digital surface model created from aerial laser scanning data. The approach consists of two steps. The first step is a MapReduce process where neighboring points in a digital surface model are mapped into cubes. The second step uses a non-MapReduce algorithm first to remove trees and other obstructions and then to extract adjacent cubes.According to this approach, all adjacent cubes belong to the same object and an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Of these technologies, airborne laser scanning (ALS) has the highest accuracy in parameterizing building morphology, ranging from simple footprint identification [17] to complicated 3D structure and roof plane modeling [14,18]. State-of-the-art ALS approaches have also achieved very high accuracy in complex urban environments by integrating aerial imagery [19], city administrative data [20], architectural knowledge [21], and the Big Data approach [22].Despite these promising results, there have been relatively few published studies on such methods being applied to large areas [23]. Furthermore, ALS data sources and aerial images are often under the control of government ministries, and, due to high operational costs, they are not available in many parts of the world [24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these technologies, airborne laser scanning (ALS) has the highest accuracy in parameterizing building morphology, ranging from simple footprint identification [17] to complicated 3D structure and roof plane modeling [14,18]. State-of-the-art ALS approaches have also achieved very high accuracy in complex urban environments by integrating aerial imagery [19], city administrative data [20], architectural knowledge [21], and the Big Data approach [22].Despite these promising results, there have been relatively few published studies on such methods being applied to large areas [23]. Furthermore, ALS data sources and aerial images are often under the control of government ministries, and, due to high operational costs, they are not available in many parts of the world [24].…”
mentioning
confidence: 99%
“…Of these technologies, airborne laser scanning (ALS) has the highest accuracy in parameterizing building morphology, ranging from simple footprint identification [17] to complicated 3D structure and roof plane modeling [14,18]. State-of-the-art ALS approaches have also achieved very high accuracy in complex urban environments by integrating aerial imagery [19], city administrative data [20], architectural knowledge [21], and the Big Data approach [22].…”
mentioning
confidence: 99%
“…In recent years, studies on building extraction, reconstruction and change detection have made significant advances and a wide range of methods have been proposed on façade segmentation and opening area detection [2], building extraction [3][4][5], change detection and map database update [1,[6][7][8], roof plane extraction [9] and 3-D reconstruction [10]. A number of techniques [11,12] have also been proposed for evaluation of these methods.…”
Section: Related Workmentioning
confidence: 99%
“…Due to that fact, Aljumaily et al [58] found out that each building appears as a deep hole by viewing the bottom view of the DEM generated by ALS data. In addition, he extracted building using this character.…”
Section: Horizontal Hollow Ratio-based Building Point Identificationmentioning
confidence: 99%